Powder recovery method
Patent Information
- Application Number
- JP2021024359
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-18
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-02-18
AI Technical Summary
【0016】 本発明の上記観点によれば、養生ヤードを不要とし、粉体の乾燥に要するエネルギーを低減し、かつ粉体中の不純物を削減することが可能となる。
Smart Images

Figure 0007644334000009 
Figure 0007644334000010 
Figure 0007644334000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for recovering powder. [Background technology]
[0002] In various manufacturing industries, including the steel industry, large amounts of mixtures in which powders containing hydrophilic particles are dispersed in water or aqueous solutions are discharged. The mixtures are often discharged in the form of aqueous slurries. The powders contained in the mixtures are diverse, and in the steel industry, for example, they include dust, scale, leach residues, fly ash, slag powder, and ore powder. All of these are also hydrophilic particles. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-132011 A [Patent Document 2] JP 2017-177018 A [Patent Document 3] JP 2018-176004 A Summary of the Invention [Problem to be solved by the invention]
[0004] Incidentally, there are cases where the powder is separated and collected from a mixture for the purpose of recycling the powder or for efficient use. In order to separate the powder from the mixture, it is necessary to remove moisture from the mixture, that is, to dry the mixture. Conventional methods for drying the mixture include a method of heating the mixture and a method of drying the mixture in the sun while plowing the mixture in a curing yard (an operation of digging up the mixture using a shovel or the like).
[0005] However, the method of drying the mixture has the problem that it takes a long time and a large amount of energy to dry the mixture because water has a high boiling point and is difficult to evaporate. In particular, high-quality (expensive) energy such as COG (coke oven gas), LNG (liquefied natural gas), heavy oil, kerosene, etc. may be used to heat the mixture, and in such cases the above problems become more serious. In addition, CO 2 CO emissions have also increased, which has become a particular issue in recent years. 2 This would also go against reductions.
[0006] On the other hand, the method of drying the mixture in the sun in a curing yard is carried out, for example, when the powder generates heat. This is to increase the safety of the powder. For example, converter dust, which is a type of dust, contains a lot of reduced iron and is prone to generating heat. For this reason, mixtures containing converter dust are often dried in the sun in a curing yard. The reduced iron in the converter dust is oxidized to stable iron oxide when dried in the sun. However, this method has the problem that not only does it require a large curing yard, but it also takes a very long time to dry the mixture. In addition, there is also the problem that it requires a large-scale and time-consuming task of plowing. Furthermore, since reduced iron, a useful iron source, was deliberately oxidized to iron oxide, its usefulness as an iron source was reduced.
[0007] In addition, a problem common to both methods is that when the mixture contains an aqueous solution, a large amount of impurities derived from the components of the aqueous solution adhere to the dried powder, resulting in a decrease in the purity of the powder. Although details will be described later, depending on the type of mixture, the liquid that disperses the powder may be an aqueous solution. For example, hot-rolled sheets are pickled in order to remove scale and internal oxide layers from the surface of the hot-rolled sheet after hot rolling. The waste liquid generated by pickling is mainly composed of pickling liquid, but may further contain powder that has been removed from the surface of the steel material by pickling, that is, leaching residue. The pickling liquid may also contain components (e.g., ions of Fe, Cr, Ni, Zn, etc.) that have leached from the steel material or the leaching residue. In this case, the mixture is composed of the leaching residue, which is a powder, and the pickling liquid, which is an aqueous solution (containing components that have leached from the steel material or the leaching residue). Then, when the mixture is dried, the components in the pickling liquid (e.g., Cr, Ni, Zn, acid components, etc.) adhere to the remaining residue. Depending on the type of mixture, the mixture may contain oil, and in this case, the same problem occurs. In other words, oil adheres to the powder after drying, and the purity of the powder decreases. Patent Documents 1 to 3 disclose techniques for recovering powder from a mixture, but these techniques cannot fully solve the above-mentioned problems.
[0008] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a new and improved method for recovering powder, which does not require a curing yard, reduces the energy required to dry the powder, and can reduce impurities in the powder. [Means for solving the problem]
[0009] In order to solve the above problems, according to one aspect of the present invention, there is provided a powder recovery method comprising: a first step of adding a hydrophobic liquid having a specific gravity greater than that of water and less than that of the powder to a first mixture of a powder containing hydrophilic particles and water or an aqueous solution, and stirring a second mixture of the first mixture and the hydrophobic liquid; a second step of applying gravity or centrifugal force by leaving the second mixture to stand, thereby separating the second mixture into an aqueous phase and a hydrophobic liquid phase, and transferring the powder to the hydrophobic liquid phase; and a third step of recovering the powder that has been transferred to the hydrophobic liquid phase.
[0010] Here, a fourth step may be included in which the powder collected in the third step is dried and the hydrophobic liquid adhering to the powder is removed.
[0011] The powder may have a volume-based 50% particle size of 100 μm or less.
[0012] In the first step, a surfactant may be added.
[0013] In addition, oil may be attached to the surface of the powder.
[0014] The boiling point of the hydrophobic liquid may be 40° C. to 95° C. at normal pressure, and the first to third steps may be carried out at normal temperature and pressure.
[0015] The powder may be any one or more selected from the group consisting of dust, scale, leaching residue, fly ash, slag powder, and ore powder. Effect of the Invention
[0016] According to the above-mentioned aspects of the present invention, it is possible to eliminate the need for a curing yard, reduce the energy required for drying the powder, and reduce impurities in the powder. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a schematic diagram for explaining an overview of the powder recovery method according to the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram for explaining modification of a powder surface by a surfactant. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] A preferred embodiment of the present invention will be described in detail below with reference to the accompanying drawings. In this specification and drawings, components having substantially the same functional configuration are denoted by the same reference numerals to avoid repetitive explanation. A numerical range expressed using "~" means a range including the numerical values before and after "~" as the lower and upper limits.
[0019] <1. Powder recovery method> First, the powder recovery method according to the present embodiment will be described with reference to Figs. 1 and 2. The powder recovery method according to the present embodiment includes first to third steps. The first step is a step of adding a hydrophobic liquid 50 having a specific gravity greater than that of water and less than that of the powder 10 to a first mixture 30 of a powder 10 containing hydrophilic particles and water or an aqueous solution (hereinafter also simply referred to as "water, etc.") 20, and stirring a second mixture of the first mixture 30 and the hydrophobic liquid 50 (Fig. 1(a)). The second step is a step of applying gravity or centrifugal force by standing to the second mixture, thereby separating the second mixture into an aqueous phase 20a and a hydrophobic liquid phase 50a, and transferring the powder 10 from the aqueous phase 20a to the hydrophobic liquid phase 50a (Fig. 1(b)). The third step is a step of recovering the powder transferred to the hydrophobic liquid phase 50a (Figs. 1(c) and (d)). Each step will be described in detail below.
[0020] (1-1. First step) In the first step, first, the hydrophobic liquid 50 is added to the first mixture 30. For example, as shown in FIG. 1(a), the first mixture 30 is poured into a container 100, and then the hydrophobic liquid 50 is poured. The order of pouring is not limited to this. Next, the second mixture, which is a mixture of the first mixture 30 and the hydrophobic liquid 50, is stirred. The degree of stirring is not important, but it is preferable to stir until the hydrophobic liquid 50 is approximately uniformly dispersed in the second mixture.
[0021] Here, the first mixture 30 contains the powder 10 and the water, etc. 20. The first mixture 30 often exists as a water-containing slurry. Of course, the first mixture 30 may be a mixture with a low powder content that is not a slurry. In other words, the first mixture 30 may be in any form as long as it contains the powder 10 and the water, etc. 20.
[0022] The powder 10 includes hydrophilic particles. The hydrophilic particles are particles that have an affinity for water and have the property of being more easily mixed with water than the hydrophobic liquid 50. The ease of mixing with water can be evaluated, for example, by the following method. That is, a predetermined amount (e.g., 1 g) of the powder 10 to be evaluated is measured and placed in a closed container together with a predetermined amount (e.g., 100 ml) of water and a predetermined amount (e.g., 100 ml) of hydrophobic liquid. Then, the mixture is thoroughly stirred and allowed to stand. The state of the aqueous phase is observed immediately after the mixture is allowed to stand, and if almost the entire amount of the powder to be evaluated is suspended in the aqueous phase, the powder to be evaluated is evaluated to be a hydrophilic particle.
[0023] The powder 10 may be composed of only hydrophilic particles, or may further contain other types of particles, such as hydrophobic particles. Here, the hydrophobic particles are particles that have an affinity for the hydrophobic liquid 50 and have the property of being more easily mixed with the hydrophobic liquid 50 than with water. The ease of mixing with the hydrophobic liquid can be evaluated, for example, by the following method. That is, a predetermined amount (for example, 1 g) of the powder 10 to be evaluated is measured and placed in a closed container together with a predetermined amount (for example, 100 ml) of water and a predetermined amount (for example, 100 ml) of the hydrophobic liquid. Then, the mixture is thoroughly stirred and allowed to stand. Immediately after the mixture is allowed to stand, the states of the water phase and the hydrophobic liquid phase are observed, and if almost the entire amount of the powder to be evaluated is suspended in the hydrophobic liquid phase, the powder to be evaluated is evaluated to be a hydrophobic particle.
[0024] When the powder to be evaluated is suspended in both the aqueous phase and the hydrophobic liquid phase, the powder can be evaluated as a mixture of hydrophilic and hydrophobic particles. Hydrophilic particles may exist independently (separately) from other types of particles, or may be combined with other types of particles to form a single particle. Examples of hydrophilic particles include coke powder and fly ash. Fly ash, which will be described later, is a type of hydrophilic particle that contains hydrophilic particles (Al 2 O 3 , SiO 2 This is an example of fly ash being composed of hydrophilic particles (unburned carbon) and hydrophobic particles (ash made of metal oxides such as iron ore). Of course, even in fly ash, hydrophilic particles and hydrophobic particles may be separated.
[0025] The true specific gravity of the powder 10 is greater than the specific gravity of the hydrophobic liquid 50 (specifically, the hydrophobic liquid 50 used to collect the powder 10). This allows the powder 10 to move to the hydrophobic liquid phase 50a in the second step described below. That is, the water, etc. 20 present between the particles of the powder 10 can be replaced with the hydrophobic liquid 50. When the powder 10 moves to the hydrophobic liquid phase 50a by performing the first and second steps described below, it can be determined that the true specific gravity of the powder 10 is greater than the specific gravity of the hydrophobic liquid 50. When hydrophobic particles are contained in the powder 10, the hydrophobic particles move to the hydrophobic liquid phase 50a.
[0026] The particle size of the powder 10 is not particularly limited, but the volumetric 50% particle size (d 50 ) is preferably 100 μm or less. Although details will be described later, in this embodiment, the water, etc. 20 present between the particles of the powder 10 is replaced with the hydrophobic liquid 50, thereby reducing the energy required to dry the powder 10 and reducing the impurities in the powder. The hydrophobic liquid 50 evaporates with lower energy than the water, etc. 20. Therefore, by replacing the water, etc. 20 present between the particles of the powder 10 with the hydrophobic liquid 50, the energy required to dry the powder 10 can be reduced. Furthermore, the impurities in the powder 10 are derived from, for example, components dissolved in the water, etc. 20. Therefore, by replacing the water, etc. 20 present between the particles of the powder 10 with the hydrophobic liquid 50, the components can be removed together with the water, etc. 20. Therefore, the impurities in the powder can be reduced. And, the smaller the particle diameter of the powder 10, the larger the gaps present between the particles of the powder 10, so that more water, etc. 20 can be replaced with the hydrophobic liquid 50. Therefore, the above-mentioned effect of performing the process of this embodiment is increased. From this viewpoint, it is preferable that the particle diameter of the powder is small. According to Experimental Example 5 described later, the volume-based 50% particle diameter (d 50 A particularly large effect can be obtained when the volume-based 50% particle diameter (d 50 ) is preferably 100 μm or less, more preferably 25 μm or less, and even more preferably 10 μm or less. On the other hand, the lower limit is preferably 1 μm or more. If the particle size is less than 1 μm, the hydrophilicity of the powder 10 becomes very high, and it may be difficult to remove the water, etc. 20 present between the particles of the powder 10 even when the treatment of this embodiment is performed.
[0027] The volumetric 50% particle size of powder 10 (d 50) can be measured, for example, by the following measurement method using a laser diffraction particle size distribution measuring device. That is, the sample to be measured is slurried with water, and a small amount of sodium hexametaphosphate solution is added as a dispersant. Next, the sample is dispersed in the mixed liquid by stirring the mixed liquid and irradiating it with ultrasonic waves. Next, this mixed liquid is placed in a laser diffraction particle size distribution measuring device, and the particle size distribution is measured. In the examples described later, the volume-based 50% particle diameter (d 50 ) was measured.
[0028] The powder 10 may be any material having the above-mentioned characteristics, but is preferably at least one selected from the group consisting of dust, scale, leaching residue, fly ash, slag powder, and ore powder, since there is a strong demand for recycling or efficient use of these powders. These powders are also hydrophilic particles.
[0029] Dusts include, for example, secondary ash generated in blast furnaces and converter dust. These dusts are often collected by wet methods, in which case a water-containing slurry is generated. In some cases, the water-containing slurry is treated with a high-concentration treatment liquid (high-concentration acid or alkali aqueous solution) to remove tramp elements (e.g., Zn) from the dust. In this case, the water-containing slurry is composed of powder containing a large amount of iron and the treatment liquid (i.e., aqueous solution).
[0030] Scale is generated, for example, during hot rolling. Specifically, scale is generated on the surface of a slab by preheating the slab. Such scale is finely crushed during hot rolling and discharged together with the coolant water. In other words, a water-containing slurry (water-containing scale) in which fine scale is dispersed in the coolant water is discharged. Note that the water-containing slurry generated during hot rolling often contains 3 to 8 mass % oil (mass % relative to the total mass of the powder). The oil adheres, for example, to the surface of the scale. The oil may also be dispersed within the water-containing slurry.
[0031] Steel materials are often surface-treated for various reasons. For example, hot-rolled sheets are pickled in order to remove scale and internal oxide layers from the surface of the hot-rolled sheets after hot rolling. Stainless steel is also pickled in order to remove scale and the like from stainless steel. The waste liquid generated by these surface treatments (pickling in the above example) is mainly composed of the surface treatment liquid (pickling liquid in the above example) used in the surface treatment, but may further contain powder that has been detached from the surface of the steel material by the surface treatment, that is, leaching residue. Furthermore, the waste liquid may contain (dissolve) components (e.g., metal ions such as Fe, Cr, Ni, and Zn) that have leached from the steel material or the leaching residue. Furthermore, the waste liquid may be subjected to some kind of treatment. For example, if the waste liquid is acidic, a neutralization treatment may be performed. When the waste liquid is neutralized, hydroxides of the components in the waste liquid may precipitate. For example, when wastewater generated from the pickling of hot-rolled steel sheets is neutralized, a mixture of hydroxides of Fe, Cr, Ni, and Zn precipitates, and when wastewater generated from the pickling of stainless steel is neutralized, hydroxides of Fe, Cr, Ni and CaF 2 A precipitate containing a mixture of these metal components is precipitated. Since the pH at which these metal components precipitate differs, a precipitate containing a specific metal component can be precipitated by adjusting the pH. Such a precipitate is also a powder and a type of leaching residue. Therefore, a surface treatment solution (corresponding to the above-mentioned aqueous solution) and a water-containing slurry containing the leaching residue are discharged by the surface treatment of the steel material. Of course, the subject of the surface treatment is not limited to the steel material. Therefore, the leaching residue in this embodiment includes powder peeled off from the treated object (steel material in the above example) by the surface treatment, as well as powder (e.g., iron hydroxide, etc.) precipitated in the waste liquid by the treatment of the waste liquid (neutralization treatment in the above example).
[0032] In addition, recycling, CO 2In recent years, there has been a strong demand for using a large amount of scrap iron from the viewpoint of reducing the amount of wastewater. Scrap iron often contains tramp elements (e.g., Cu, Zn, Ni, etc.). For this reason, when scrap iron is used, the scrap iron is treated in advance with a high-concentration treatment liquid (e.g., high-concentration ammonia water for Cu, Zn, Ni) which is a leaching agent for the tramp elements, so that the tramp elements in the scrap iron are leached into the high-concentration treatment liquid as ions (e.g., ammine complex ions, metal ions, etc.). This removes the tramp elements from the scrap iron. Therefore, the tramp elements are dissolved in the waste liquid after the treatment. On the other hand, since the waste liquid is a high-concentration treatment liquid, the tramp elements are often precipitated, and the tramp element leaching ability of the high-concentration treatment liquid is regenerated and reused. In this case, H is added to the waste liquid, which is, for example, high-concentration ammonia water. 2 S gas is passed through the waste liquid to precipitate the tramp elements in the waste liquid as sulfides. As a result, a water-containing slurry is produced in which powder precipitates (which can be interpreted as a type of leaching residue as mentioned above) are dispersed in the waste liquid.
[0033] Fly ash is a powder generated during power generation at coal-fired power plants. Fly ash contains Al 2 O 3 , SiO 2 The ash, which is made up of metal oxides such as carbides, contains unburned carbon, which is a carbon component that remains after burning. Fly ash is made up of hydrophilic particles (Al 2 O 3 , SiO 2 This is an example of a mixture of hydrophilic and hydrophobic particles (unburned carbon) and ash (metal oxides such as mercury). Of course, even in fly ash, hydrophilic and hydrophobic particles may be separated. Fly ash may be collected after removing hydrophobic particles from the fly ash using a wet method, in which case a water-containing slurry containing the fly ash is discharged. 2 O 3In order to remove these substances, the aqueous slurry is sometimes treated with an acid under heat and pressure. In this case, the aqueous slurry is composed of fly ash and an aqueous solution of an acid. The aqueous solution of the acid contains components leached from the fly ash, such as Al ions.
[0034] Slag powder is generated, for example, in blast furnaces. Specifically, the slag generated in blast furnaces is often wet-ground (so-called water granulation). By such water granulation, a water-containing slurry in which the slag powder is dispersed is generated.
[0035] In the steel industry, ore dressing may be performed to improve the quality of iron ore, which is a raw material for steel. In summary, ore dressing is a process in which iron ore is crushed and then ore powder with a high iron content is separated. Ore dressing may be performed wet, in which case an aqueous slurry is generated in which the ore powder is dispersed in water. In the non-ferrous field, raw materials such as copper oxide ore, zinc concentrate, bauxite, pyrrhotite, etc. may be treated with a leaching agent such as acid, alkali, or ammonia to leach and separate target components or impurities from these raw materials. In this case, an aqueous slurry is generated in which the ore powder is dispersed in an aqueous solution.
[0036] The water, etc. 20 is water or an aqueous solution. The composition of the water, etc. 20 varies depending on the mixture. For example, when the powder 10 is dust, scale, fly ash, slag powder, or ore powder, the water, etc. 20 is often water. However, when some component (e.g., acid, alkali, or ammonia) is added to the water, etc. 20, the water, etc. 20 becomes an aqueous solution. The aqueous solution may contain components that have leached from the powder 10. For example, Al may be leached from the fly ash. 2 O 3 In some cases, the aqueous slurry is treated with hydrochloric acid to remove the above-mentioned impurities. In this case, the aqueous slurry is composed of fly ash and an aqueous solution of an acid. The aqueous solution of the acid contains components leached from the fly ash, such as Al ions. On the other hand, when the powder 10 becomes a leaching residue, the water, etc. 20 is almost always an aqueous solution.
[0037] As described above, when the water or the like 20 becomes an aqueous solution, there is a problem that the purity of the powder 10 after drying decreases. For example, the waste liquid generated by pickling of a hot-rolled sheet may further contain, in addition to the pickling liquid which is a surface treatment liquid, a powder detached from the surface of the hot-rolled sheet by pickling, that is, a leaching residue. Furthermore, the waste liquid may contain components leached from the steel material or the leaching residue (e.g., metal ions such as Fe, Cr, Ni, Zn, etc.). In this case, the mixture is composed of the leaching residue which is a powder and the pickling liquid which is an aqueous solution (containing components leached from the steel material or the leaching residue). Then, when the mixture is dried, the components in the pickling liquid (e.g., Cr, Ni, Zn, etc.) adhere to the residual residue. Furthermore, when the waste liquid generated by pickling of a hot-rolled sheet is neutralized, hydroxides of metal components in the waste liquid precipitate. Since the pH at which these metal components precipitate differ, it is possible to precipitate a precipitate containing a specific metal component by adjusting the pH. For example, it is possible to precipitate only iron hydroxide by adjusting the pH of the waste liquid. However, other metal components (e.g., Cr, Ni, Zn, etc.) remain as ions in the waste liquid. Therefore, when attempting to recover the iron hydroxide powder by drying, the metal components remaining as ions in the waste liquid adhere to the iron hydroxide powder. Depending on the type of mixture, the mixture may contain oil, and in this case, the same problem occurs. That is, the oil adheres to the powder after drying, and the purity of the powder decreases. In this embodiment, the purity of the powder 10 can be increased by replacing such an aqueous solution with the hydrophobic liquid 50. In particular, when a specific metal component is selectively precipitated, such a specific metal component can be recovered with high purity.
[0038] The hydrophobic liquid 50 is a liquid having hydrophobicity, that is, a liquid having a property of having low affinity for water (difficult to dissolve in water or difficult to mix with water). The hydrophobic liquid 50 is, for example, a liquid having a solubility in water of 0 g / L or more and 10.0 g / L or less at room temperature (25° C.). If the solubility of the hydrophobic liquid 50 in water is high, when the water, etc. 20 present between the particles of the powder 10 is replaced with the hydrophobic liquid 50, a large amount of the water, etc. 20 remains in the hydrophobic liquid 50. In this case, there is a possibility that the energy required for drying the powder 10 cannot be sufficiently reduced. From this viewpoint, the solubility of the hydrophobic liquid 50 in water is preferably 10.0 g / L or less at room temperature, and more preferably 5.0 g / L or less. In this case, the water, etc. 20 remaining in the hydrophobic liquid 50 can be further reduced.
[0039] In the present embodiment, the term "hydrophobic" includes lipophilicity. The hydrophobic liquid 50 may be, for example, an organic solvent or various oils having hydrophobic properties.
[0040] The solubility of the hydrophobic liquid 50 is often determined by data published by the manufacturer of the hydrophobic liquid, but it can also be measured as follows. For example, 15 ml of water and the hydrophobic liquid are placed in a 50 ml centrifuge tube with a stopper, and shaken at 150 revolutions per minute for 1 hour in a thermostatic bath at 25°C. The mixture is then centrifuged (1,750G, 5 minutes), and the mixture after centrifugation is allowed to stand in a thermostatic bath at 25°C for about 1 hour. An arbitrary amount of the aqueous phase is then taken, and the amount of the solvent in the water is measured by gas chromatography-mass spectrometry (GC / MS). This makes it possible to determine the solubility of the hydrophobic liquid in water. In the following examples, the solubility of the hydrophobic liquid 50 published by the manufacturer of the hydrophobic liquid is used.
[0041] The specific gravity of the hydrophobic liquid 50 is greater than that of water and less than that of the powder 10 to be collected. As a result, after the second step described below is performed, the liquid phase in the container 100 becomes the aqueous phase 20a and the hydrophobic liquid phase 50a from the top, and the powder 10 moves into the hydrophobic liquid phase 50a. The specific gravity of the hydrophobic liquid 50 may be, for example, about 1.05 or more and 1.8 or less. The powder 10 may be porous. Therefore, when selecting the hydrophobic liquid 50, the first and second steps may be actually performed using a candidate hydrophobic liquid 50. Then, as a result of the second step, if the liquid phase in the container 100 becomes the aqueous phase 20a and the hydrophobic liquid phase 50a from the top, and the powder 10 moves into the hydrophobic liquid phase 50a, the hydrophobic liquid 50 may be selected. Only one type of hydrophobic liquid 50 may be used, or multiple types may be mixed and used.
[0042] The boiling point of the hydrophobic liquid 50 is preferably higher than the temperature of the first mixture 30 under the same pressure condition. This allows the first to third steps to be performed stably. If the boiling point of the hydrophobic liquid 50 is equal to or lower than the temperature of the first mixture 30 under the same pressure condition, a large amount of the hydrophobic liquid 50 evaporates when the hydrophobic liquid 50 is added to the first mixture 30. In this case, it may be time-consuming to mix the first mixture 30 and the hydrophobic liquid 50. Furthermore, the first mixture 30 may contain a highly volatile component (such as hydrochloric acid). For example, the above-mentioned pickling may be performed with hydrochloric acid, in which case the first mixture 30 contains highly volatile hydrochloric acid. When the first mixture 30 contains a highly volatile component, it is preferable to perform the treatment of this embodiment in a sealed working environment from the viewpoint of ensuring the safety of the worker. Therefore, if the boiling point of the hydrophobic liquid 50 is equal to or lower than the temperature of the first mixture 30 under the same pressure condition, a large amount of the hydrophobic liquid 50 evaporates when the hydrophobic liquid 50 is added to the first mixture 30, and the internal pressure of the test environment may increase. Therefore, the boiling point of the hydrophobic liquid 50 is preferably higher than the temperature of the first mixture 30 under the same pressure conditions.
[0043] For example, when the temperature of the first mixture 30 is room temperature (25°C), the boiling point of the hydrophobic liquid 50 is preferably 40°C or higher and lower than 200°C under the same pressure condition. The upper limit of the boiling point is more preferably lower than 100°C, and even more preferably lower than 95°C. When the upper limit of the boiling point is lower than 100°C, the hydrophobic liquid 50 can be easily removed (for example, with water vapor, which is an inexpensive energy source) in the third step described below. In other words, when the first to third steps are performed at room temperature and normal pressure, the boiling point of the hydrophobic liquid 50 is preferably 40°C to 95°C at normal pressure.
[0044] In addition, when the temperature of the first mixture 30 is more than 100°C and less than 230°C, the boiling point of the hydrophobic liquid 50 is preferably 30 to 100°C higher than the temperature of the first mixture 30 under the same pressure condition. Alternatively, the hydrophobic liquid 50 may be added to the first mixture 30 after cooling the first mixture 30. In this case, the boiling point of the hydrophobic liquid 50 is preferably 30 to 100°C higher than the temperature of the first mixture 30 after cooling. For example, the acid treatment of fly ash and the acid treatment of ore powder may be performed under heating and pressure, and in these cases, the waste liquid may be heated to more than 100°C and less than 230°C. If the boiling point of the hydrophobic liquid 50 is 30 to 100°C higher than the temperature of the first mixture 30, the first to third steps can be stably performed even in such a working environment (environment under heating and pressure). The hydrophobic liquid 50 may be added to the first mixture 30 after the temperature of the first mixture 30 is lowered. In this case, as described above, the boiling point of the hydrophobic liquid 50 is preferably 30 to 100°C higher than the temperature of the first mixture 30 after the temperature is lowered. Therefore, even if the first mixture 30 contains a highly volatile component, the first to third steps can be performed without significantly changing the internal pressure of the sealed working environment. This means that the first to third steps can be performed without changing or significantly changing the working environment. Therefore, a series of operations from the operation that generates the first mixture 30 (for example, the acid treatment of fly ash) to the collection of the powder can be performed in the same working environment, which is very efficient. The first mixture 30 may be cooled to room temperature and the first to third steps may be performed at room temperature and normal pressure, but this operation is laborious and time-consuming.
[0045] Moreover, the volatile heat value of the hydrophobic liquid 50 is preferably smaller than that of water. In this case, the hydrophobic liquid 50 can be easily removed by volatilization in the third step, and can be easily separated from the powder 10.
[0046] Furthermore, when the powder 10 contains oil, it is preferable to separate the oil from the powder 10 as well. In this case, therefore, it is preferable to select a hydrophobic liquid 50 with a KB value (kauri-butanol value) as large as possible. This is because a hydrophobic liquid 50 with a large KB value easily absorbs oil. In other words, the oil in the powder 10 is absorbed into the hydrophobic liquid 50 in the first and second steps. Then, in the third step, the hydrophobic liquid 50 is removed together with the oil.
[0047] Note that the preferred KB value cannot be generally specified because it varies depending on various factors such as the composition of the oil content, etc. Therefore, among the prepared hydrophobic liquids 50, the one with the largest KB value may be selected.
[0048] The method for measuring the KB value is as follows. First, a certain amount of Kauri resin butanol solution is placed in an Erlenmeyer flask and placed on a standard type paper. Next, a sample (hydrophobic liquid) is added to the Kauri resin butanol solution in the Erlenmeyer flask, and the number of ml of the sample (hydrophobic liquid) when the solution becomes turbid and the type becomes unreadable is taken as the KB value. The larger the KB value, the stronger the oil and fat dissolving power of the hydrophobic liquid 50. The KB value is considered to be an indicator of the cleaning power of dry cleaning solvents against oily stains. In this embodiment, the KB value is used as an index for selecting the hydrophobic liquid 50. As shown in the examples described later, when the first mixture 30 contains oil, it is preferable to use a hydrophobic liquid 50 with a high KB value, such as trichloroethylene or 1-bromopropane.
[0049] Any hydrophobic liquid 50 that satisfies the above conditions can be applied to this embodiment. Examples of the hydrophobic liquid 50 include trichloroethylene, 1-bromopropane, tetrachloroethylene, various fluorine-based organic solvents (e.g., 1-ethoxy-1,1,2,2,3,3,4,4,4-nonafluorobutane, 1,1,1,2,2,3,3,4,4,5,5,6,6,-tridecafluorooctane, hydrofluoroether, etc.).
[0050] The effect of this embodiment can be obtained even if the amount of hydrophobic liquid 50 added to the first mixture 30 is small. However, if the amount of hydrophobic liquid 50 added is too small, only a small amount of powder 10 can be moved to the hydrophobic liquid phase 50a in the second step. Therefore, the effect of this embodiment may not be fully obtained. Therefore, it is preferable to set the amount of hydrophobic liquid 50 added so that the entire amount of powder 10 is immersed in the hydrophobic liquid phase 50a after the second step. This makes it possible to obtain the effect of this embodiment more effectively.
[0051] In this embodiment, as described later, the powder 10 containing hydrophilic particles is moved to the hydrophobic liquid phase 50a. Therefore, in order to increase the affinity between the powder 10 and the hydrophobic liquid phase 50a, it is preferable to add a surfactant 60 (see FIG. 2) to the first mixture 30 in addition to the hydrophobic liquid 50. For example, the hydrophobic liquid 50 to which the surfactant 60 has been added is added to the first mixture 30. The manner in which the surfactant 60 is added is not particularly limited. For example, the surfactant 60 may be added to the first mixture 30 separately from the hydrophobic liquid 50.
[0052] As shown in FIG. 2, the surfactant 60 has a hydrophilic group 61 and a hydrophobic group 62. The hydrophilic group 61 of the surfactant 60 faces the surface side of the powder 10, and the hydrophobic group 62 faces the outside of the powder 10. This can change the surface of the powder 10 from hydrophilic to hydrophobic, so that the amount of water, etc. 20 accompanying the powder 10 can be reduced when the powder 10 is moved from the aqueous phase 20a to the hydrophobic liquid phase 50a. That is, more water, etc. 20 can be replaced with the hydrophobic liquid 50. As a result, the energy required for drying the powder 10 can be further reduced. Note that FIG. 2 shows the state in which the surface of the powder 10 is modified by the surfactant 60, and the powder 10 is moved to the hydrophobic liquid phase 50a. It can be seen that the water, etc. 20 is not attached to the part of the surface of the powder 10 to which the surfactant 60 is attached. Therefore, the energy required for drying the powder 10 in the third step can be further reduced. As a result, it is expected that the cost of drying will be reduced and the dryness will be improved. Furthermore, when the water or the like 20 becomes an aqueous solution, the amount of impurities (each component in the aqueous solution) that migrates to the hydrophobic liquid phase 50a together with the powder 10 will also be reduced, and preferably completely removed.
[0053] The surfactant usable in this embodiment is an oil-soluble surfactant, and is mainly an anionic surfactant, but may also be a cationic surfactant, an amphoteric surfactant, or a nonionic surfactant. More specific examples include sodium sulfonate (also called Na sulfonate), calcium sulfonate (also called Ca sulfonate), magnesium sulfonate (also called Mg sulfonate), and the like, which are oil-soluble anionic surfactants. Only one type of surfactant may be used, or multiple types may be used in combination. It is preferable that the surfactant is stable at the temperature at which the surfactant is used, that the functional group portion is ionized at the pH of the first mixture 30, and that the surfactant dissolves in the hydrophobic liquid 50 at the temperature at which the surfactant is used at 1 mg / L or more, more preferably 1 g / L or more. When actually selecting a surfactant, the first to third steps are actually performed using a surfactant that is a candidate for use, and a surfactant that requires less energy to dry the powder 10 may be selected. In addition, the amount of surfactant added is not particularly limited. As shown in the examples described later, the more surfactant is added, the more water or the like 20 can be replaced with the hydrophobic liquid 50. As a result, it is possible to further reduce the energy required to dry the powder 10. However, as the amount of surfactant added increases, the reduction in the amount of energy required to dry the powder 10 reaches a plateau. The amount of surfactant added at this time becomes a substantial upper limit.
[0054] (1-2. Second step) In the second step, as shown in FIG. 1(b), gravity or centrifugal force due to standing is applied to the second mixture, so that the second mixture is separated into an aqueous phase 20a and a hydrophobic liquid phase 50a. Furthermore, the powder 10 is moved from the aqueous phase 20a to the hydrophobic liquid phase 50a. The magnitude and time of the centrifugal force may be adjusted to such an extent that the second mixture exhibits the above-mentioned behavior. When centrifugal force is applied to the second mixture, the second mixture can be separated into the aqueous phase 20a and the hydrophobic liquid phase 50a in a shorter time than gravity. Therefore, it is preferable to apply centrifugal force to the second mixture. There is no particular limit to the upper limit of the centrifugal force, but since there are almost no centrifugal separators that can be applied when the centrifugal force exceeds 10,000 G, it is preferable that the centrifugal force is 10,000 G or less. In addition, the centrifugal separator to be applied may be a filtration type centrifuge.
[0055] The second step causes the powder 10 to move to the hydrophobic liquid phase 50a. At this time, much of the water, etc. 20 present around the powder 10, particularly the water, etc. 20 present between the particles of the powder 10, is replaced by the hydrophobic liquid 50. By adding a surfactant 60 to the hydrophobic liquid 50, a larger amount of the water, etc. 20 can be replaced by the hydrophobic liquid 50. If oil is present between the particles or on the surfaces of the powder 10, the oil is absorbed into the hydrophobic liquid.
[0056] (1-3. Third step) In the third step, the powder 10 transferred to the hydrophobic liquid phase 50a is collected. Specifically, as shown in Fig. 1(b) and (c), the part of the hydrophobic liquid phase 50a where the powder 10 is aggregated (this part is often cake-like. Hereinafter, this part is also referred to as "powder cake") is separated and collected from the other parts of the second mixture (the aqueous phase 20a and the parts of the hydrophobic liquid phase 50a other than the powder cake). In the example of Fig. 1(c), the collected powder cake is transferred to another container 200.
[0057] Next, the powder cake is dried to remove the hydrophobic liquid 50 from the powder cake (fourth step), as shown in FIG. 1(d), and the powder 10 is recovered. Here, since most of the liquid contained in the powder cake is the hydrophobic liquid 50, the powder cake can be dried with less energy (amount of heat of vaporization). Therefore, the CO 2 can be reduced. Even if the water, etc. 20 constituting the first mixture 30 becomes an aqueous solution, the amount of water, etc. 20 carried into the powder cake is reduced. In addition, if the first mixture contains oil, the oil is absorbed into the hydrophobic liquid 50 in the second step and is removed together with the hydrophobic liquid in the third step. Therefore, impurities (impurities derived from the components of the aqueous solution and oil) remaining in the powder 10 can be reduced. In addition, a curing yard is not required to collect the powder 10. As shown in the examples described later, the energy required to dry the powder 10 can be measured by differential scanning calorimetry (DSC), but it can also be measured by other methods, such as the Karl Fischer method.
[0058] The temperature and pressure when carrying out the first to third steps are not particularly limited, and may be carried out, for example, at room temperature and pressure. However, when the first mixture is produced under heating and pressure, the first to third steps may be carried out in the same environment. In this case, the preferred properties of the hydrophobic liquid 50 are as described above. EXAMPLES
[0059] <1. Experimental Example 1 (Removal of water between particles)> Next, examples (experimental examples) of this embodiment will be described. In each of the experimental examples described below, various tests were performed to confirm the effects of this embodiment. Note that each of the experimental examples below was performed under normal temperature and pressure.
[0060] In Examples 1-2 to 1-8, first, fly ash containing 3.5% by mass of unburned carbon relative to the total mass of the fly ash was heated to 600°C under atmospheric conditions to combust the unburned carbon present in the fly ash. The decarbonized fly ash (decarbonized FA) thus obtained was made into a powder. The decarbonized FA was a powder containing SiO 2 59.5% by mass (% by mass relative to the total mass of decarbonated FA), Al 2 O 3 24.2% by mass, Fe 2 O 3 The powder is an oxide particle containing 6.7 mass% of C-FA, and is mostly spherical particles with a volume-based 50% particle diameter of 7 μm. Here, the chemical components of the C-FA-free powder were measured by ICP method after dissolving the dried C-FA-free powder in an acidic aqueous solution. The volume-based 50% particle diameter was measured by the method described above. The laser diffraction particle size distribution analyzer used was LA-960 (manufactured by Horiba, Ltd.).
[0061] Trichloroethylene or 1-bromopropane was used as the hydrophobic liquid. Trichloroethylene has a specific gravity of 1.46, a solubility in water of 1.28g / L at room temperature, a boiling point of 87°C at room temperature, and a KB value of 130. 1-bromopropane has a specific gravity of 1.35, a solubility in water of 2.5g / L at room temperature, a boiling point of 71°C at room temperature, and a KB value of 125.
[0062] Next, 20 g of dried decarbonated FA and 150 ml of water were added to a 500 ml container to form a slurry. That is, a first mixture was prepared. Next, the pH of the first mixture was measured. Next, 150 ml of a hydrophobic liquid (trichloroethylene or 1-bromopropane) and a surfactant (Na sulfonate solution diluted with trichloroethylene or 1-bromopropane) were added to the first mixture, and the mixture of these, called the second mixture, was stirred for 30 seconds by a high-shear stirring homogenizer.
[0063] The second mixture was then placed in a centrifuge tube, and centrifugal force (1,750 G) was applied to the second mixture by a centrifuge for 30 seconds. This caused the second mixture to separate into an aqueous phase and a hydrophobic liquid phase, and the de-C-FA moved from the aqueous phase to the hydrophobic liquid phase. The de-C-FA settled to the bottom of the centrifuge tube and became cake-like. The centrifuge tube was then tilted to discharge the aqueous phase and hydrophobic liquid phase present on the upper side of the powder cake.
[0064] Next, a part (5-8 mg) of the powder cake deposited at the bottom of the centrifuge tube was collected as a sample, and the sample was immediately set in a differential scanning calorimetry (DSC) device (DSC8230, manufactured by Rigaku Corporation) while still wet. Next, the sample was heated from room temperature to 80°C, and the heat of vaporization at this time was measured. Since the amount of sample was very small, the hydrophobic liquid in the sample, which is easily volatile, evaporates between the weighing operation and the differential scanning calorimetry measurement. For this reason, it is presumed that the measured heat of vaporization is the heat of vaporization due only to the moisture in the sample. In any case, it can be said that the smaller the heat of vaporization, the smaller the amount of water etc. brought into the powder cake, and the less energy is required to dry the powder cake. In addition, in Examples 1-2 to 1-8, similar tests were performed by changing the pH of the first mixture, the type of hydrophobic liquid, the type of surfactant, and the additive rate of the surfactant (addition rate to the powder). The heat of vaporization for each sample was a low value of 400 J / g-dry. The test conditions and heat of vaporization are shown in Table 1. The test conditions and heat of vaporization for Comparative Example 1-1 and Example 1-9 described below are also shown in Table 1.
[0065] On the other hand, in Comparative Example 1-1, the first mixture used in Example 1-2 (i.e., one to which neither hydrophobic liquid nor surfactant was added) was put into a centrifuge tube, and the first mixture was subjected to centrifugal force (1,750 G) for 30 seconds by a centrifuge. As a result, the C-FA-removed product was precipitated at the bottom of the centrifuge tube. Then, the centrifuge tube was tilted to discharge the aqueous phase. Then, the powder cake precipitated at the bottom was collected. The moisture content of the collected powder cake was 34 mass% (mass% relative to the total mass of the powder cake). In addition, when the heat of vaporization of the powder cake was measured by differential scanning calorimetry in the same manner as in Examples 1-2 to 1-8, the heat of vaporization was 538 J / g-dry, which was higher than that of Examples 1-2 to 1-8. The moisture content of the powder cake was determined by drying the powder cake in a thermostatic chamber at 105° C. and calculating the reduction in mass before and after drying ((mass before drying−mass after drying) / (mass before drying)).
[0066] In Example 1-9, the same experiment as in Example 1-5 was performed except that the fly ash (FA) used in Examples 1-2 to 1-8 was powdered without being burned (i.e., without being decarbonized and converted to FA). The heat of vaporization of the powder cake was 80 J / g-dry, which was also lower than that of Comparative Example 1-1.
[0067] Comparing Comparative Example 1-1 and Example 1-2, the heat of vaporization in Example 1-2 was smaller than that in Comparative Example 1-1. In Example 1-2, water and the like present between the C-FA-free particles was replaced with a hydrophobic liquid. On the other hand, such a treatment was not performed in Comparative Example 1-1. Therefore, in Example 1-2, the amount of water and the like present between the particles was reduced, and the heat of vaporization was reduced. Furthermore, in Examples 1-3 to 1-8 in which a surfactant was added, the surface of the C-FA-free particles was made hydrophobic by the addition of the surfactant. Therefore, when the water and the like present between the C-FA-free particles was replaced with a hydrophobic liquid, more water and the like could be replaced with the hydrophobic liquid. The larger the surfactant addition rate, the smaller the heat of vaporization. Therefore, the larger the surfactant addition rate, the more water and the like could be replaced with the hydrophobic liquid. In Example 1-6, the heat of vaporization was 0 J / g-dry, so that there was substantially no water and the like present between the C-FA-free particles. Therefore, in Examples 1-6, it is believed that the surfactant made the entire surface of the C-FA-free particles hydrophobic, and all water etc. between the particles was replaced by a hydrophobic liquid.
[0068] In addition, comparing Example 1-6, in which the hydrophobic liquid used is trichloroethylene, with Example 1-8, in which the hydrophobic liquid used is 1-bromopropane, the heat of vaporization of Example 1-6 was smaller, even though the surfactant addition rate of Example 1-8 was sufficiently large. This is considered to be because the solubility of trichloroethylene in water is smaller than that of 1-bromopropane in water. That is, in Example 1-6, when the water, etc. present between the C-FA-free particles is replaced with the hydrophobic liquid, the amount of water, etc. taken up by the hydrophobic liquid is less than that of Example 1-8. Specifically, in Example 1-6, the heat of vaporization is 0 J / g-dry, so the amount of water, etc. taken up by the hydrophobic liquid is almost zero, whereas in Example 1-8, the heat of vaporization is larger than 0 J / g-dry, so it is considered that a small amount of water is taken up by the hydrophobic liquid.
[0069] In addition, in Example 1-9, fly ash (FA) is used as the powder, but the water and the like present between the particles of the decarbonated FA are replaced with a hydrophobic liquid as in Examples 1-2 to 1-8. Therefore, in Example 1-9, the amount of water and the like present between the particles is reduced, and the heat of vaporization is reduced. However, compared with Example 1-5, which is the same condition as Example 1-9 except for the powder, the heat of vaporization of Example 1-9 is larger than that of Example 1-5. Therefore, it is considered that more water and the like remains between the particles of the fly ash in Example 1-9. Fly ash contains hydrophobic particles (unburned carbon) in addition to hydrophilic particles. Therefore, it is considered that most of the surfactant adheres to the hydrophobic particles and does not adhere sufficiently to the hydrophilic particles. Therefore, it is considered that the surface of the hydrophilic particles is not sufficiently hydrophobic, and water and the like remains between the hydrophilic particles.
[0070] Next, about 10 g of each sample was taken from the powder cakes obtained in Comparative Example 1-1, Example 1-4, and Example 1-6, and each sample was placed in a thermostatic dryer and allowed to stand while maintaining the temperature inside the dryer at 105°C. Furthermore, the mass change of each sample was measured in this state, and the time it took for the mass to become constant was measured. In this test, since the mass of each sample was as large as 10 g, each sample contained not only water, etc. (water, etc. remaining after replacement with hydrophobic liquid) but also trichloroethylene, which is a hydrophobic liquid, when placed in the dryer. Therefore, in this test, the time required to remove the water, etc. and hydrophobic liquid contained in each sample was measured. As a result, it was 54 minutes in Comparative Example 1-1, 16 minutes in Example 1-4, and 6 minutes in Example 1-6. Therefore, by replacing the water, etc. present between the particles of the powder with the hydrophobic liquid, the energy required to dry the powder (i.e., the heat of vaporization) was reduced. In other words, it was found that the powder became easier to dry and the drying speed of the powder increased.
[0071] [Table 1]
[0072] <2. Experimental Example 2 (Removal of water and other substances present between particles of blast furnace gas ash after removing zinc from the blast furnace gas ash with alkali)> In Examples 2-2 to 2-6, first, blast furnace gas ash containing 39 mass% Fe, 28 mass% C, and 1.3 mass% Zn relative to the total mass of the blast furnace gas ash and having a volume-based 50% particle size of 18 μm was prepared as a powder. Here, the chemical components of the blast furnace gas ash were measured by ICP method after dissolving the dried blast furnace gas ash in an acidic aqueous solution. The volume-based 50% particle size was measured by the above-mentioned method.
[0073] Next, Zn, a tramp element, was removed from the blast furnace gas ash. Specifically, 20 g of blast furnace gas ash, 200 ml of water, ammonium sulfate containing ammonium ions that convert Zn into an ammine complex, and NaOH were added to a 500 ml container to form a slurry. Next, the NH 3 The concentration was adjusted to 30 g / L and the pH to 10.5, and the slurry was stirred with a shaker for 3 hours in a sealed container. This allowed Zn to be leached from the blast furnace gas ash into the aqueous solution. In other words, a first mixture was prepared.
[0074] Next, 200 ml of hydrophobic liquid (1-bromopropane) and surfactant (Ca sulfonate solution diluted with trichloroethylene) were added to the container. Next, the mixture of these, called the second mixture, was stirred for 30 seconds using a high-shear stirring homogenizer. After that, the second mixture was placed in a centrifuge tube, and centrifugal force (1,750G) was applied to the second mixture for 30 seconds using a centrifuge. As a result, the second mixture was separated into an aqueous phase and a hydrophobic liquid phase, and the blast furnace gas ash moved from the aqueous phase to the hydrophobic liquid phase. The blast furnace gas ash settled at the bottom of the centrifuge tube and became cake-like. Next, the centrifuge tube was tilted to discharge the aqueous phase and hydrophobic liquid phase present on the upper side of the powder cake.
[0075] Next, a portion (5-8 mg) of the powder cake deposited at the bottom of the centrifuge tube was collected as a sample, and the sample was immediately set in a differential scanning calorimeter while still wet. The differential scanning calorimeter used was the same as that used in Experimental Example 1. Next, the sample was heated from room temperature to 80°C, and the heat of vaporization at this time was measured.
[0076] Further, the powder cake was put into a thermostatic dryer, and the temperature inside the dryer was maintained at 105°C to dry the powder cake. Next, the Zn and S contents (mass% relative to the total mass of the powder cake after drying) in the dried powder cake were measured. The measurement was performed by ICP method after dissolving the dried powder cake in an acidic aqueous solution. Note that Zn and S are components contained in the aqueous solution of the first mixture, and the lower their contents, the fewer impurities contained in the powder. Zn was leached from the blast furnace gas ash into the aqueous solution of the first mixture, and S originated from sulfate ions in ammonium sulfate, which is a leaching agent for leaching Zn into the aqueous solution. Table 2 shows the test conditions, heat of vaporization, Zn content, and S content of Examples 2-2 to 2-6.
[0077] In Comparative Example 2-1, the first mixture prepared above (i.e., one to which neither hydrophobic liquid nor surfactant was added) was placed in a centrifuge tube, and the first mixture was subjected to centrifugal force (1,750 G) by a centrifuge for 30 seconds. Then, the centrifuge tube was tilted to discharge the aqueous phase. Then, the powder cake that had settled at the bottom was collected. Thereafter, the same treatment as in Examples 2-2 to 2-6 was performed to measure the heat of vaporization, Zn content, and S content. The test conditions, heat of vaporization, Zn content, and S content of Comparative Example 2-1 are shown in Table 2.
[0078] In both Comparative Example 2-1 and Examples 2-2 to 2-6, the Zn content was reduced from the initial Zn content (1.3 mass%) contained in the blast furnace gas ash. Therefore, in all examples, at least Zn was removed. However, when comparing Comparative Example 2-1 with Examples 2-2 to 2-6, the heat of vaporization in Comparative Example 2-1 was higher than that in Examples 2-2 to 2-6, and both the Zn content and S content in Comparative Example 2-1 were higher than those in Examples 2-2 to 2-6.
[0079] First, comparing Comparative Example 2-1 and Example 2-2, in Example 2-2, water and the like present between the particles of blast furnace gas ash are replaced with a hydrophobic liquid. On the other hand, such a treatment is not performed in Comparative Example 2-1. Therefore, in Example 2-2, the amount of water and the like (here, aqueous solution) present between the particles is reduced, and the heat of vaporization is reduced. Furthermore, since Zn and S dissolved in water and the like are also replaced by the hydrophobic liquid together with the water and the like, the Zn content and S content are also reduced. Furthermore, in Examples 2-3 to 2-6 in which a surfactant is added, the surface of the particles of blast furnace gas ash is made hydrophobic by the addition of the surfactant. Therefore, when the water and the like present between the particles of blast furnace gas ash is replaced with the hydrophobic liquid, more water and the like can be replaced with the hydrophobic liquid. Therefore, the heat of vaporization, Zn content, and S content are further reduced. Furthermore, the greater the surfactant addition rate, the lower the heat of vaporization, Zn content, and S content. In Example 2-6, the heat of vaporization was 10 J / g-dry, which means that a small amount of water, etc. was present between the blast furnace gas ash particles. In Example 2-6, it is believed that the surfactant made all the surfaces of the blast furnace gas ash particles hydrophobic, and all the water, etc. between the particles was replaced with the hydrophobic liquid, but it is believed that such a result was obtained because a small amount of water, etc. was dissolved in the hydrophobic liquid.
[0080] [Table 2]
[0081] <3. Experimental Example 3 (Removal of water and other substances present between particles of blast furnace gas ash after removing zinc from blast furnace gas ash with acid)> In Examples 3-2 to 3-6, first, Zn, which is a tramp element, was removed from the blast furnace gas ash used in Experimental Example 2. Specifically, 20 g of blast furnace gas ash and 200 ml of water were added to a 500 ml container to form a slurry. Next, a hydrochloric acid solution with a concentration of 36 mass% was added to the slurry to adjust the pH of the slurry to 1. Next, the slurry was stirred with a shaker for 1 hour with the container sealed. This caused Zn to be leached from the blast furnace gas ash into the aqueous solution. That is, a first mixture was prepared.
[0082] Next, 200 ml of a hydrophobic liquid (1-ethoxy-1,1,2,2,3,3,4,4,4-nonafluorobutane, which is a fluorine-based organic solvent) and a surfactant (Mg sulfonate liquid diluted with the fluorine-based organic solvent) were added to the container. Here, the specific gravity of 1-ethoxy-1,1,2,2,3,3,4,4,4-nonafluorobutane is 1.43, its solubility in water is 20 mg / L at room temperature, its boiling point at room temperature is 76°C, and its KB value is 10. Next, the second mixture, which is a mixture of these, was stirred for 30 seconds using a high-shear stirring homogenizer. After that, the second mixture was put into a centrifuge tube, and centrifugal force (1,750 G) was applied to the second mixture using a centrifuge for 30 seconds. As a result, the second mixture was separated into an aqueous phase and a hydrophobic liquid phase, and the blast furnace gas ash moved from the aqueous phase to the hydrophobic liquid phase. The blast furnace gas ash settled to the bottom of the centrifuge tube and formed a cake, and then the centrifuge tube was tilted to drain the aqueous phase and hydrophobic liquid phase present on the upper side of the powder cake.
[0083] Next, a portion (5-8 mg) of the powder cake deposited at the bottom of the centrifuge tube was collected as a sample, and the sample was immediately set in a differential scanning calorimeter while still wet. The differential scanning calorimeter used was the same as that used in Experimental Example 1. Next, the sample was heated from room temperature to 80°C, and the heat of vaporization at this time was measured.
[0084] Further, the powder cake was put into a thermostatic dryer, and the temperature inside the dryer was maintained at 105°C to dry the powder cake. Then, the Zn and Cl contents (mass % relative to the total mass of the powder cake after drying) in the dried powder cake were measured. The Zn content was measured by ICP method after dissolving the dried powder cake in an acidic aqueous solution. The Cl content was measured by extracting the Cl component by extracting the dried powder cake with hot water and then by ion chromatography. Note that Zn and Cl are components contained in the aqueous solution of the first mixture, and the lower their contents, the fewer the impurities contained in the powder. Zn was leached from the blast furnace gas ash into the aqueous solution of the first mixture, and Cl was derived from hydrochloric acid, which is a leaching agent for leaching Zn into the aqueous solution. Table 3 shows the test conditions, heat of vaporization, Zn content, and Cl content of Examples 3-2 to 3-6.
[0085] In Comparative Example 3-1, the first mixture prepared above (i.e., one to which neither hydrophobic liquid nor surfactant was added) was put into a centrifuge tube, and the first mixture was subjected to centrifugal force (1,750 G) by a centrifuge for 30 seconds. Then, the centrifuge tube was tilted to discharge the aqueous phase. Then, the powder cake deposited at the bottom was collected. Thereafter, the same treatment as in Examples 3-2 to 3-6 was performed to measure the heat of vaporization, Zn content, and Cl content. The test conditions, heat of vaporization, Zn content, and Cl content of Comparative Example 3-1 are shown in Table 3.
[0086] In both Comparative Example 3-1 and Examples 3-2 to 3-6, the Zn content was reduced from the Zn content (1.3 mass%) contained in the initial blast furnace gas ash. Therefore, in all examples, at least Zn was removed. However, when comparing Comparative Example 3-1 with Examples 3-2 to 3-6, the heat of vaporization in Comparative Example 3-1 was higher than that in Examples 3-2 to 3-6, and the Zn content and S content in Comparative Example 3-1 were both higher than those in Examples 3-2 to 3-6.
[0087] First, comparing Comparative Example 3-1 and Example 3-2, in Example 3-2, water and the like present between the particles of the blast furnace gas ash are replaced with a hydrophobic liquid. On the other hand, such a treatment is not performed in Comparative Example 3-1. Therefore, in Example 3-2, the amount of water and the like (here, an aqueous solution) present between the particles is reduced, and the heat of vaporization is reduced. Furthermore, since Zn and Cl dissolved in the water and the like are also replaced by the hydrophobic liquid together with the water and the like, the Zn content and the Cl content are also reduced. Furthermore, in Examples 3-3 to 3-6 in which a surfactant is added, the surface of the particles of the blast furnace gas ash is made hydrophobic by the addition of the surfactant. Therefore, when the water and the like present between the particles of the blast furnace gas ash are replaced with the hydrophobic liquid, more water and the like can be replaced with the hydrophobic liquid. Therefore, the heat of vaporization, the Zn content, and the Cl content are further reduced. Furthermore, the heat of vaporization, the Zn content, and the Cl content are reduced as the surfactant addition rate is increased. In Example 3-6, the heat of vaporization was 0 J / g-dry, which means that there is substantially no water or the like between the particles of the blast furnace gas ash. Therefore, in Example 3-6, it is considered that the surfactant makes all the surfaces of the blast furnace gas ash particles hydrophobic, and all the water or the like between the particles is replaced with a hydrophobic liquid.
[0088] [Table 3]
[0089] <4. Experimental Example 4 (Removal of water and oil between particles)> In Examples 4-2 to 4-5, first, a water-containing slurry containing oil (oil-containing slurry) was prepared as a first mixture. Here, the scale in the water-containing slurry contained 63 mass% Fe and 3.1 mass% oil with respect to the total mass of the scale, and the particle size at 50% by volume was 48 μm. Here, the chemical components of the scale were measured by ICP method after dissolving the dried scale in an acidic aqueous solution. The oil content of the scale was measured by the following method. That is, the dried scale was immersed in normal hexane to extract the oil from the scale. Then, the extraction liquid was heated to 100° C. to volatilize the normal hexane, and the oil content was calculated from the amount of residue. The particle size at 50% by volume was measured by the above-mentioned method.
[0090] Next, 150 ml of the first mixture (52 g solid matter) and 200 ml of hydrophobic liquid (1-bromopropane) were placed in a 500 ml container, and the mixture, called the second mixture, was stirred for 30 seconds using a high-shear stirring homogenizer. Next, a surfactant (Na sulfonate solution diluted with 1-bromopropane) was added to the second mixture, and the second mixture was stirred for another 30 seconds using a high-shear stirring homogenizer. Thereafter, the second mixture was placed in a centrifuge tube, and centrifugal force (1,750 G) was applied to the second mixture using a centrifuge for 30 seconds. As a result, the second mixture was separated into an aqueous phase and a hydrophobic liquid phase, and the scale moved from the aqueous phase to the hydrophobic liquid phase. The scale settled at the bottom of the centrifuge tube and became cake-like. Next, the centrifuge tube was tilted to drain the aqueous phase and hydrophobic liquid phase present on the upper side of the powder cake.
[0091] Next, a portion (5-8 mg) of the powder cake deposited at the bottom of the centrifuge tube was collected as a sample, and the sample was immediately set in a differential scanning calorimeter while still wet. The differential scanning calorimeter used was the same as that used in Experimental Example 1. Next, the sample was heated from room temperature to 80°C, and the heat of vaporization at this time was measured.
[0092] The powder cake was then placed in a thermostatic dryer, and the temperature inside the dryer was maintained at 105°C to dry the powder cake. The oil content (mass % relative to the total mass of the dried powder cake (excluding oil)) was then measured. The oil content was measured by the method described above. Table 4 shows the test conditions, heat of vaporization, and oil content for Examples 4-2 to 4-5.
[0093] In Comparative Example 4-1, 150 ml (solid amount 52 g) of the first mixture (i.e., aqueous slurry to which no hydrophobic liquid or surfactant was added) was placed in a centrifuge tube, and the first mixture was subjected to centrifugal force (1,750 G) for 30 seconds using a centrifuge. The centrifuge tube was then tilted to discharge the aqueous phase. The powder cake that had settled at the bottom was then collected. Thereafter, the same treatment as in Examples 4-2 to 4-5 was performed to measure the heat of vaporization and the oil content. The test conditions, heat of vaporization, and oil content of Comparative Example 4-1 are shown in Table 4.
[0094] Comparing Comparative Example 4-1 with Examples 4-2 to 4-5, in Comparative Example 4-1, the oil content did not change from the original oil content of the scale, and the oil was not removed. Furthermore, the heat of vaporization in Comparative Example 4-1 was higher than that in Examples 4-2 to 4-5. On the other hand, in Examples 4-2 to 4-5, the oil content was greatly reduced in all cases, and it was found that the oil was removed. The heat of vaporization also greatly decreased.
[0095] First, comparing Comparative Example 4-1 and Example 4-2, in Example 4-2, water and the like present between the particles of the scale is replaced with a hydrophobic liquid. On the other hand, such a treatment is not performed in Comparative Example 4-1. Therefore, in Example 4-2, the amount of water and the like present between the particles is reduced, and the heat of vaporization is reduced. In addition, the oil present between the particles is absorbed into the hydrophobic liquid and is removed together with the hydrophobic liquid. Therefore, the oil content is also reduced. However, when the hydrophobic liquid is removed, some of the oil dissolved in the hydrophobic liquid may remain. Therefore, a small amount of oil remains in Example 4-2.
[0096] Furthermore, in Examples 4-3 to 4-5 in which a surfactant was added, the surface of the scale particles became hydrophobic due to the addition of the surfactant. Therefore, when the water, etc. present between the scale particles was replaced with the hydrophobic liquid, more water, etc. could be replaced with the hydrophobic liquid. Therefore, the heat of vaporization was further reduced. Furthermore, the heat of vaporization was reduced as the surfactant addition rate was increased. Therefore, the more water, etc. could be replaced with the hydrophobic liquid as the surfactant addition rate was increased. In Example 4-5, the heat of vaporization was 13 J / g-dry, so that a small amount of water, etc. was present between the scale particles. In Example 4-5, it is considered that the surfactant made all the surfaces of the scale particles hydrophobic, and all the water, etc. between the particles was replaced with the hydrophobic liquid, but it is considered that such a result was obtained because a small amount of water, etc. was dissolved in the hydrophobic liquid.
[0097] On the other hand, the oil content increased slightly with an increase in the surfactant addition rate. The greater the surfactant addition rate, the more hydrophobic liquid containing oil is present between the particles. Therefore, the greater the surfactant addition rate, the more oil remains when the hydrophobic liquid is removed. Of course, the mass % of the oil content in each of Examples 4-2 to 4-5 is significantly reduced compared to Comparative Example 4-1, and the effect of this embodiment is fully obtained.
[0098] [Table 4]
[0099] <5. Experimental Example 5 (d 50 (Consideration of the impact of) In Examples 5-2, 5-4, and 5-6, the volume-based 50% particle size (d 50 Fine sand with different volumetric 50% particle diameter (d 50 ) are shown in Table 5. The fine sand is SiO 2 and Al 2 O 3In Examples 5-8 and 5-10, several kinds of fly ashes with different chemical compositions and 50% particle sizes on a volume basis were heated to 600°C under atmospheric conditions to combust the unburned carbon present in each fly ash. The several kinds of decarbonized FA thus obtained were made into powder. These decarbonized FAs were SiO 2 52 to 64 mass% (mass% relative to the total mass of decarbonated FA), Al 2 O 3 19 to 28 mass% Fe 2 O 3 The oxide particles contain 3 to 8 mass % of C-FA, and contain many spherical particles. Furthermore, the volumetric 50% particle diameters of these C-FA-free oxide particles are different from each other. The volumetric 50% particle diameters (d 50 ) are shown in Table 5. The chemical components of the fine sand and the decarbonized FA were measured by ICP method after dissolving the fine sand and the decarbonized FA in an acidic aqueous solution after drying. The volume-based 50% particle diameter (d 50 ) was measured by the method described above.
[0100] Next, in Examples 5-2, 5-4, 5-6, 5-8, and 5-10, 20 g of dried powder and 150 ml of water were added to a 500 ml container to form a slurry. That is, a first mixture was prepared. Next, the pH of the first mixture was measured. The pH was 7.1 to 8.9. Next, 150 ml of hydrophobic liquid (trichloroethylene) was added to the first mixture, and the mixture, that is, the second mixture, was stirred for 30 seconds by a high-shear stirring homogenizer. Thereafter, the second mixture was placed in a centrifuge tube, and centrifugal force (1,750 G) was applied to the second mixture by a centrifuge for 30 seconds. As a result, the second mixture was separated into an aqueous phase and a hydrophobic liquid phase, and the powder (fine sand or de-C-FA) moved from the aqueous phase to the hydrophobic liquid phase. The powder settled to the bottom of the centrifuge tube and became cake-like. The centrifuge tube was then tilted to discard the aqueous and hydrophobic liquid phases present on top of the powder cake.
[0101] Next, a part (5-8 mg) of the powder cake deposited at the bottom of the centrifuge tube was taken as a sample, and the sample was immediately set in a differential scanning calorimeter while still wet. The differential scanning calorimeter used was the same as that used in Experimental Example 1. Next, the sample was heated from room temperature to 80°C, and the heat of vaporization at this time was measured. The test conditions and heat of vaporization for Examples 5-2, 5-4, 5-6, 5-8, and 5-10 are shown in Table 5.
[0102] In Example 5-11, the second mixture prepared in Example 5-2 was left to stand for 2 minutes instead of being centrifuged. In other words, in Example 5-11, gravity was applied to the second mixture by leaving it to stand. In Example 5-11, the second mixture in the container was also separated into an aqueous phase and a hydrophobic liquid phase, and the powder (fine sand) moved from the aqueous phase to the hydrophobic liquid phase. The powder settled to the bottom of the centrifuge tube and became cake-like. Thereafter, the heat of vaporization of the powder cake was measured by differential scanning calorimetry in the same manner as in Example 5-2. The test conditions and heat of vaporization of Example 5-11 are shown in Table 5.
[0103] In Comparative Examples 5-1, 5-3, and 5-5, the first mixture (i.e., without the addition of hydrophobic liquid) prepared in Examples 5-2, 5-4, and 5-6 was placed in a centrifuge tube, and the first mixture was subjected to centrifugal force (1,750 G) for 30 seconds by a centrifuge. This caused the powder to settle at the bottom of the centrifuge tube. The centrifuge tube was then tilted to discharge the aqueous phase. The powder cake that had settled at the bottom was then collected. The heat of vaporization of the powder cake was then measured by differential scanning calorimetry in the same manner as in Examples 5-2, 5-4, and 5-6. Table 5 shows the test conditions and heat of vaporization of Comparative Examples 5-1, 5-3, and 5-5.
[0104] In Comparative Examples 5-7 and 5-9, the first mixture (i.e., without adding hydrophobic liquid) prepared in Examples 5-8 and 5-10 was placed in a centrifuge tube, and the first mixture was subjected to centrifugal force (1,750G) for 30 seconds by a centrifuge. This caused the powder to settle at the bottom of the centrifuge tube. The centrifuge tube was then tilted to discharge the aqueous phase. The powder cake that had settled at the bottom was then collected. The heat of vaporization of the powder cake was then measured by differential scanning calorimetry in the same manner as in Examples 5-8 and 5-10. The test conditions and heat of vaporization of Comparative Examples 5-7 and 5-9 are shown in Table 5.
[0105] When comparing each example with a comparative example using the same powder as in these examples (for example, comparing Example 5-2 with Comparative Example 5-1), the heat of vaporization in each example was lower than that of the corresponding comparative example. In each example, the water, etc. present between the powder particles was replaced with a hydrophobic liquid. On the other hand, such treatment was not performed in each comparative example. As a result, in each example, there was less water, etc. present between the particles, and the heat of vaporization was smaller. Furthermore, the smaller the volumetric 50% particle size of the powder, the greater the decrease in the heat of vaporization, and the decrease was particularly significant when the volumetric 50% particle size was 100 μm or less, 25 μm or less, or 10 μm or less. Therefore, the volumetric 50% particle size of the powder (d 50 It has been found that the thickness is preferably 100 μm or less, more preferably 25 μm or less, and even more preferably 10 μm or less.
[0106] Furthermore, when comparing Comparative Example 5-1, Example 5-2, and Example 5-11, it was confirmed that the heat of vaporization also decreased in Example 5-11, in which the fine sand was allowed to settle by standing still, but the heat of vaporization did not decrease as much as in Example 5-2, in which centrifugal force was applied.
[0107] [Table 5]
[0108] <6. Example 6 (Removal of water and the like present between particles of slag powder or iron ore powder)> In Examples 6-2 and 6-4, slag powder or ore powder was prepared as the powder. Here, the slag powder was obtained by wet grinding slag generated from a blast furnace. The slag powder contained 41.7 mass% CaO (mass% relative to the total mass of the slag powder), SiO 2 33.8% by mass, Al 2 O 3 The slag powder is an oxide particle containing 13.4 mass% of Fe and has a 50% volumetric particle diameter of 67 μm. The chemical components of the slag powder were measured using an X-ray fluorescence analyzer (XRF) (ZSX PrimusII, manufactured by Rigaku Corporation) using the glass bead method. The 50% volumetric particle diameter was measured using the method described above. On the other hand, the ore powder is iron ore powder. The iron ore powder contains Fe 2 O 3 The oxide particles contain 89.4 mass% (mass% relative to the total mass of the iron ore powder), and the 50% particle size based on volume is 110 μm. Here, the chemical components of the iron ore powder were measured by ICP method after dissolving the dried iron ore powder in an acidic aqueous solution. The 50% particle size based on volume was measured by the above-mentioned method.
[0109] Next, 20 g of dried powder and 150 ml of water were added to a 500 ml container to form a slurry. That is, a first mixture was prepared. Next, the pH of the first mixture was measured. Next, 150 ml of a hydrophobic liquid (trichloroethylene) and a surfactant (Na sulfonate solution diluted with trichloroethylene) were added to the first mixture, and the mixture, which was a second mixture, was stirred for 30 seconds by a high-shear stirring homogenizer. Thereafter, the second mixture was placed in a centrifuge tube, and centrifugal force (1,750 G) was applied to the second mixture by a centrifuge for 30 seconds. As a result, the second mixture was separated into an aqueous phase and a hydrophobic liquid phase, and the powder moved from the aqueous phase to the hydrophobic liquid phase. The powder settled to the bottom of the centrifuge tube and became a cake. Next, the centrifuge tube was tilted to discharge the aqueous phase and the hydrophobic liquid phase present on the upper side of the powder cake.
[0110] Next, a portion (5-8 mg) of the powder cake deposited at the bottom of the centrifuge tube was collected as a sample, and the sample was immediately set in a differential scanning calorimeter while still wet. The differential scanning calorimeter used was the same as that used in Experimental Example 1. Next, the sample was heated from room temperature to 80°C, and the heat of vaporization at this time was measured. The test conditions and heat of vaporization for Examples 6-2 and 6-4 are shown in Table 6.
[0111] In Comparative Examples 6-1 and 6-3, the first mixture (i.e., without the addition of hydrophobic liquid and surfactant) prepared in Examples 6-2 and 6-4 was put into a centrifuge tube, and the first mixture was subjected to centrifugal force (1,750 G) for 30 seconds by a centrifuge. This caused the powder to settle at the bottom of the centrifuge tube. Then, the centrifuge tube was tilted to discharge the aqueous phase. Then, the powder cake that had settled at the bottom was collected. Then, the moisture content of the collected powder cake was measured in the same manner as in Experimental Example 1, and the moisture content was 34 mass% (mass% relative to the total mass of the powder cake). Furthermore, the heat of vaporization of the powder cake was measured by differential scanning calorimetry in the same manner as in Examples 6-2 and 6-4. The test conditions and heat of vaporization of Comparative Examples 6-1 and 6-3 are shown in Table 6.
[0112] When comparing each Example with a Comparative Example using the same powder as the Example (for example, comparing Example 6-2 with Comparative Example 6-1), the heat of vaporization in each Example was lower than that of the corresponding Comparative Example. In each Example, water and the like present between the powder particles was replaced with a hydrophobic liquid. On the other hand, in each Comparative Example, such a treatment was not performed. As a result, in each Example, there was less water and the like present between the particles, and the heat of vaporization was smaller.
[0113] [Table 6]
[0114] <7. Experimental Example 7 (Example of powder becoming leaching residue)> First, the leaching solution (leaching agent) of ammonium sulfate (20 g-NH 3 / L (converted ammonia concentration) was placed in a leaching vessel, and the pH was adjusted to 9.8 to 10.2 with a 20% by mass NaOH aqueous solution. Furthermore, a surface-treated steel sheet (surface area 0.08 m2) plated with Zn and Ni was placed in the leaching vessel. 2 ) was added, and the mixture was stirred for 3 hours with the stirring pump. After that, the stirring pump was stopped, and the inside of the leaching vessel was left to stand. Next, the leachate in the leaching vessel was discharged from the leaching vessel and filtered to obtain a leachate waste liquid. The composition of the leachate waste liquid is shown in Table 7. As shown in Table 7, the leachate waste liquid contains NH 3 In addition, it contains Zn and Ni ions (which exist as ammine complex ions) that have leached out from the surface-treated steel sheets. The concentrations of Zn and Ni in the leachate were measured by the ICP method, and the NH 3 The concentration was measured by the spectrophotometric method for the distillate after distillation, and the S concentration in the leachate was 2- The concentration was measured by iodometric titration after distillation.
[0115] Next, the leaching waste liquid was placed in a regeneration vessel, and hydrogen sulfide gas was added to the leaching waste liquid while stirring with a stirring pump until the redox potential became -200 mV. As a result, Zn ions and Ni ions forming ammine complex ions were precipitated as sulfides (Zn sulfide and Ni sulfide). At that time, the pH of the leaching waste liquid was measured with a pH meter, and the pH of the leaching waste liquid was maintained at 9.8 to 10.2. The hydrogen sulfide concentration in the gas phase in the regeneration vessel was 0.1 ppm or less. A first mixture was produced by the above steps. Here, the powder is the leaching residue, i.e., Zn sulfide and Ni sulfide (sulfide particles), and the water, etc. is the leaching waste liquid.
[0116] Next, 200 ml of the first mixture was placed in a 500 ml container, and further, 200 ml of hydrophobic liquid (trichloroethylene) and 0.6 mass% of Na sulfonate liquid relative to the amount of precipitated sulfide were added to the container. Next, the mixture of these, the second mixture, was stirred for 30 seconds by a high-shear stirring homogenizer. After that, the second mixture was placed in a centrifuge tube, and centrifugal force (1,750 G) was applied to the second mixture by a centrifuge for 30 seconds. As a result, the second mixture was separated into an aqueous phase and a hydrophobic liquid phase, and the leaching residue moved from the aqueous phase to the hydrophobic liquid phase. The leaching residue settled at the bottom of the centrifuge tube and became cake-like. Next, the centrifuge tube was tilted to discharge the aqueous phase and hydrophobic liquid phase present on the upper side of the powder cake.
[0117] The discharged aqueous phase and hydrophobic liquid phase were then transferred to a separate container and separated into two phases by gravity separation while standing. The aqueous phase (i.e., the leachate excluding the leachate residue) was then collected. The composition of the leachate excluding the leachate residue is shown in Table 7. The measurement method was the same as above. As shown in Table 7, the NH 3 The concentration is the NH 3 The concentrations of Zn and Ni in the leachate from which the leachate residue was removed were approximately the same as those in the leachate from which the leachate was removed, and no sulfide ions derived from hydrogen sulfide gas were detected. On the other hand, the concentrations of Zn and Ni in the leachate from which the leachate residue was removed were significantly reduced, reaching values at which the leachate could be reused. Therefore, it was confirmed that the leachate used in Experimental Example 7 has the function of leaching Zn and Ni, and that the leachate from which the leachate was reused as a leachate by the treatment of this Experimental Example 7 (the treatment of this embodiment).
[0118] Next, a portion (5 mg) of the powder cake deposited at the bottom of the centrifuge tube was taken as a sample, and the sample was immediately set in a differential scanning calorimeter while still wet. The differential scanning calorimeter used was the same as that used in Experimental Example 1. Next, the sample was heated from room temperature to 80°C, and the heat of vaporization at this time was measured. As a result, the heat of vaporization was 125 J / g-dry.
[0119] On the other hand, the first mixture (i.e., the leaching waste liquid containing the leaching residue and to which no hydrophobic liquid or surfactant was added) was placed in a centrifuge tube, and the first mixture was subjected to centrifugal force (1,750 G) by a centrifuge for 30 seconds. The centrifuge tube was then tilted to discharge the aqueous phase. The powder cake that had settled at the bottom was then recovered. The same process as above was then performed, and the heat of vaporization was measured. As a result, the heat of vaporization was 735 J / g-dry. Therefore, it was confirmed that even when the powder becomes a sulfide-based leaching residue, the heat of vaporization can be significantly reduced by replacing the water, etc. present between the powder particles with a hydrophobic liquid.
[0120] [Table 7]
[0121] Example 8 (CaF from leaching wastewater after stainless steel treatment) 2 Recovery)> A Cr-Ni stainless steel was used as the stainless steel, and a fluoride ion-containing waste liquid was prepared during pickling. The composition of the fluoride ion-containing waste liquid is shown in Table 8. The Fe, Cr, and Ni concentrations in the fluoride ion-containing waste liquid were measured by ICP method, and the F concentration in the fluoride ion-containing waste liquid was measured by ion chromatography.
[0122] Next, 10 L of the fluoride ion-containing waste liquid was placed in a container, and quicklime (CaO) was added while stirring the fluoride ion-containing waste liquid to adjust the pH of the fluoride ion-containing waste liquid to 3. As a result, the fluoride ions in the fluoride ion-containing waste liquid were converted to CaF 2 The fluoride ion-containing waste liquid was then left to stand, and the CaF 2 The precipitate, the main component of which was CaF, was precipitated. The supernatant was then discarded to prepare the first mixture, a water-containing slurry. The powder in this mixture was the precipitate (main component was CaF), the leaching residue. 2 ) and water etc. is a waste liquid containing fluoride ions.
[0123] Next, 200 ml of the first mixture was placed in a 500 ml container, and further, 200 ml of hydrophobic liquid (trichloroethylene) and 1.0 mass % of Na sulfonate liquid relative to the amount of precipitated solids were added to the container. Next, the mixture of these, the second mixture, was stirred for 30 seconds using a high-shear stirring homogenizer. Thereafter, the second mixture was placed in a centrifuge tube, and centrifugal force (1,750 G) was applied to the second mixture using a centrifuge for 30 seconds. As a result, the second mixture was separated into an aqueous phase and a hydrophobic liquid phase, and the leaching residue moved from the aqueous phase to the hydrophobic liquid phase. The leaching residue settled at the bottom of the centrifuge tube and became cake-like. Next, the centrifuge tube was tilted to discharge the aqueous phase and hydrophobic liquid phase present on the upper side of the powder cake.
[0124] Next, a portion (5 mg) of the powder cake deposited at the bottom of the centrifuge tube was taken as a sample, and the sample was immediately set in a differential scanning calorimeter while still wet. The differential scanning calorimeter used was the same as that used in Experimental Example 1. Next, the sample was heated from room temperature to 80°C, and the heat of vaporization at this time was measured. As a result, the heat of vaporization was 39 J / g-dry.
[0125] On the other hand, the first mixture (i.e., the leaching waste liquid containing the leaching residue and to which no hydrophobic liquid or surfactant was added) was placed in a centrifuge tube, and the first mixture was subjected to centrifugal force (1,750 G) by a centrifuge for 30 seconds. The centrifuge tube was then tilted to drain the aqueous phase. The powder cake that had settled at the bottom was then collected. The same process as above was then carried out to measure the heat of vaporization. As a result, the heat of vaporization was 693 J / g-dry. Therefore, it was confirmed that the powder was CaF 2 It was confirmed that even if the leaching residue is mainly composed of, by replacing the water and other substances present between the powder particles with a hydrophobic liquid, the heat of vaporization can be significantly reduced.
[0126] [Table 8] [Explanation of symbols]
[0127] 10 powder 20 Water etc. 20a aqueous phase 30 First mixture 50 Hydrophobic Liquid 50a Hydrophobic liquid phase 100, 200 containers
Claims
1. a first step of adding a hydrophobic liquid having a specific gravity greater than that of water and less than that of the powder to a first mixture of a powder containing hydrophilic particles and water or an aqueous solution, and stirring a second mixture of the first mixture and the hydrophobic liquid; a second step of applying gravity or centrifugal force to the second mixture by standing to separate the second mixture into an aqueous phase and a hydrophobic liquid phase and transferring the powder to the hydrophobic liquid phase; and a third step of recovering the powder that has been transferred to the hydrophobic liquid phase; the powder containing hydrophilic particles is any one or more selected from the group consisting of dust, scale, leach residue, fly ash, slag powder, and ore powder, or when 1 g of the powder is put into a sealed container together with 100 ml of water and 100 ml of the hydrophobic liquid, the mixture is stirred and allowed to stand, and the state of the aqueous phase is observed, the powder at least floats in the aqueous phase, the hydrophobic liquid is trichloroethylene, 1-bromopropane, tetrachloroethylene, a fluorine-based organic solvent, or a liquid whose solubility in water at room temperature (25° C.) is 0 g / L or more and 10.0 g / L or less, In the first step, a surfactant is added, After the second step, the entire amount of the powder is immersed in the hydrophobic liquid phase. A method for recovering powder comprising the steps of:
2. 2. The powder recovery method according to claim 1, further comprising a fourth step of drying the powder recovered in the third step to remove the hydrophobic liquid adhering to the powder.
3. 3. The method for recovering powder according to claim 1, wherein the powder has a volume-based 50% particle size of 100 μm or less.
4. A method for recovering powder described in any one of claims 1 to 3, wherein the surfactant is an oil-soluble anionic surfactant.
5. The method for recovering powder according to any one of claims 1 to 4, characterized in that oil is attached to the surface of the powder.
6. The boiling point of the hydrophobic liquid is 40° C. to 95° C. at normal pressure; The powder recovery method according to any one of claims 1 to 5, wherein the first step to the third step are carried out at room temperature and normal pressure.
Citation Information
Patent Citations
Oil sludge treatment method
CN112079540A
Rolling and machining sludge degreasing solvent, degreasing method and apparatus therefor
JP2000355718A
Apparatus and method for treating oil stuck particle
JP2003071205A
Oil content separating method, and oil content separating device
JP2015132011A
Emulsion breakdown device, emulsion breakdown method, and oil content separation device
JP2017177018A